A Study on Intercultural and modern technology-based education - Swati Garg (AG Volumes, 2022)
In order to help students/future teachers grow as individuals and as members of society, training programs increasingly emphasize the development of students’ interpersonal and intercultural competencies. Within the study of optional courses, one of the component parts of students’ first training programs for teaching positions Intercultural Education at the forefront of the list of priorities. This may be explained by the necessity to train/develop certain individuals who are cognizant of their origins, so that they can have landmarks to help them find their place in the world. Education is one of several fields in which technological improvements have opened up new possibilities for human endeavor. When it comes to education, especially in the area of teaching, the advent of technology has resulted in a shift in the trend away from conventional teaching approaches and toward a more contemporary digital teaching style.